Reverse-transcription loop-mediated isothermal amplification for rapid detection of respiratory syncytial virus directly from nasopharyngeal swabs - Hoos, Johannes; Peters, Rebecca; Tabatabai, Julia; Grulich-Henn, Jürgen; Schnitzler, Paul; Pfeil, Johannes (Journal of virological methods, 2017)
Respiratory syncytial virus (RSV) is a common cause of lower respiratory tract infection in young infants and a major cause of nosocomial infection in pediatric care. Currently available RSV point-of-care tests are of limited sensitivity and relatively expensive. We developed and evaluated a novel RSV rapid test for use at point-of-care, based on reverse-transcription loop-mediated isothermal amplification (RT-LAMP) for direct testing of nasopharyngeal swab specimens. RT-LAMP can detect RSV within 30min, without the need for RNA extraction. The sensitivity of our RT-LAMP assay was 70-80% in comparison to RT-PCR. The RT-LAMP test sensitivity is at least equivalent to currently available rapid antigen detection tests (RADT), and the cost of RT-LAMP test reagents is only approximately 10% of that of commercially available RADT tests. RT-LAMP appears to be an attractive alternative to RADT, particularly in settings with limited financial resources. Future improvements could include lyophilization of test reagents and automated read-out of RT-LAMP results.
Gesehen am 30.08.2018